A Correlation Study of Reading Comprehension with Speaking Skill in English Class at Vocational High School - Siti Uswatun Khasanah; Rizka Safriyani (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
Students in vocational high school are required to learn their vocational skills and English as a Foreign Language in preparation for their potential profession or job. This research investigates the relationship between reading comprehension and speaking skills in English classes and the degree to which reading comprehension relates to vocational high school students' speaking abilities. Thirty-five students from a vocational high school in Surabaya participated in the study. This study's design was a correlation study, and it was performed using a descriptive quantitative method. The students were given a test to assess their abilities. The results of this study indicated that there was a connection between reading comprehension and speaking ability. The correlation coefficient was 0.61, and the correlation was strong. The teacher should have greater access to what they are reading, and improved reading resources would aid their communication skills.Keyword:  Correlation, Reading Comprehension, Speaking Skill